Implications of the regulation of the prostitutional system in sexual equality: the german case - Nuño Gómez, Laura (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: The abolition of prostitution has been an objective and a historical demand of both the feminist movement and feminist political theory. However, the proposal of consideration as any other activity in the framework of labor relations, is now portrayed as an urgent regulatory innovation aimed, supposedly, at guaranteeing the rights of prostituted women. But this claim must be interpreted in relation with the transformation of prostitution as an activity, which currently represents a lucrative global market with systemic dimensions. This article analyzes the structural components of the prostitution system and the implications of its regulation on gender equality in order to evaluate the particular effects of its regulation in the German case.
Keywords: Prostitution; Trafficking in Human Beings; THB; Public Policies Sexual Exploitation; Gender Equality; Public Interantional Law